Estudo das propriedades químicas, elétricas e da microestrutura de filmes de óxidos coloridos crescidos sobre aço inoxidável por processos químico e eletroquímicos - Kikuti, Elaine (Universidade Federal de São Carlos, 2006)
In the present work, it was studied the chemical composition, morphology, structure and semiconductor properties of oxide films coloured by the chemical - CHE and electrochemical processes (triangular current scan - TCS, alternating potential pulse - APP and superposition of ac and dc signals - SPS) before and after a hardening treatment. Oxide films with two distinct values of thickness (~130 nm e ~200 nm) were obtained using the CHE, TCS and APP colouration processes. The SPS process produced oxide films with only one value of thickness (~150 nm). The hardening treatment led to an increase in the thickness values of the oxide films produced by all the investigated processes (CHE, TCS, APP and SPS). Polarization curves showed that the hardening treatment also promotes enrichment in chromium oxide in the oxide films. This was supported by analyses of chemical composition obtained by Auger spectroscopy (AES) and X-ray photoelectron spectroscopy (XPS). Moreover, these analyses also showed that iron and chromium oxides mainly constitute all oxide films, before and after the hardening treatment. By other hand, images obtained by electron transmission microscopy (TEM) revealed that more compact oxide films are produced after the hardening treatment. Patterns of electron diffraction revealed that the oxide films are constituted of nanocrystalline FeCr2O4 spinel oxide, before and after the hardening treatment. The Mott-Schottky plots presented a quite complex behavior with three straight regions for all the oxide films studied. From these plots two distinct flat band potentials were obtained, being one in the passive region (-0,50 V vs. ECS) and other in the transpassive region (0.50 V vs. SCE) of the stainless steel. These flat band potentials are characteristics of iron and chromium oxides, respectively. Besides, two semiconductivity transitions were observed: transition from p-type to n-type (p-n heterojunction) at -0.50 V vs. ECS and transition from n-type to ptype at 0.0 V vs. SCE. Values of band gap energy in the range 2.94 eV - 3.49 eV were calculated assuming direct transitions only for the hardened oxide films produced by the distinct processes.
Study of the chemical and electrical properties and of the microstructure of coloured oxide films grown on stainless steel by chemical and electrochemical process
Keywords: Eletroquímica; Filmes de óxido; Ácido inoxidável austenítico; Propriedades semicondutoras; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA::ELETROQUIMICA